Brain Structural and Functional Dissociated Patterns in Degenerative Cervical Myelopathy: A Case-Controlled Retrospective Resting-State fMRI Study - Zhou, Yi; Shi, Jiaqi (Frontiers in Neurology, 2022)
Background Previous studies have identified the global functional connectivity density (gFCD) and gray matter volume (GMV) aberrations in degenerative cervical myelopathy (DCM) patients. Untill now, to our knowledge there is no study has investigated the associations between the spatial distribution patterns of GMV and gFCD alterations. Methods Structural data and resting-state functional MRI scanning of 35 DCM patients and 35 matched healthy controls were collected to assess gFCD and GMV. We investigated alterations in spatial pattern in gFCD and GMV among DCM patients and their associated spatial distributions. Results In our current study, we found that gFCD and GMV were both affected in some regions of the visual system, sensorimotor cortices and cerebellum. More importantly, in our findings, decreased gFCD was found in areas primarily located in the sensorimotor cortices, while increased gFCD was observed primarily in areas located in the visual system and cerebellum. Decreased GMV was seen in the left thalamus, bilateral SMA, and left inferior occipital cortices in patients with DCM, while increased GMV was observed in the cerebellum. Conclusions Our findings suggest that structural and functional alterations probably contribute independently to the neurobiology of DCM. However, the nature of the associations between the structural deficits and functional alterations needs clarification using longitudinal studies to pinpoint the onset of connectivity abnormalities as DCM develops.